2022
DOI: 10.1155/2022/8831750
|View full text |Cite
|
Sign up to set email alerts
|

Natural Herbal Medicine as a Treatment Strategy for Myocardial Infarction through the Regulation of Angiogenesis

Abstract: Aim of Study. Myocardial infarction is the number one cause of death worldwide. Existing treatment methods such as drugs and surgery cannot completely restore the structure and function of the ischemic heart. In recent years, therapeutic angiogenesis has received gradually increasing attention due to its fundamental therapeutic advantages of improving microcirculation and restoring blood supply in ischemic areas. This article mainly reviewed the mechanism and effect of angiogenesis-promoting herbs. Methods. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 159 publications
0
5
0
Order By: Relevance
“…Several studies had shown that therapeutic angiogenesis may be an effective strategy for management of ischemic diseases such as MI, particularly for patients who are not eligible for traditional methods of revascularization (Moghiman et al 2021 ; Spadaccio et al 2022 ; Zhang et al 2022 ). This strategy involves restoring perfusion to ischemic regions through stimulation of neovascularization and maturation of preexisting vasculature into functional ones (Moghiman et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies had shown that therapeutic angiogenesis may be an effective strategy for management of ischemic diseases such as MI, particularly for patients who are not eligible for traditional methods of revascularization (Moghiman et al 2021 ; Spadaccio et al 2022 ; Zhang et al 2022 ). This strategy involves restoring perfusion to ischemic regions through stimulation of neovascularization and maturation of preexisting vasculature into functional ones (Moghiman et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Extensive clinical evidences supported that blood-activating and stasis-removing drugs provided excellent efficacy in improving microvascular function and clinical prognosis (Fang et al, 2022;Wang et al, 2021; M. X. Zhang et al, 2022). Whitmania pigra Whitman was mostly utilized in the localized venous congestion settings related to flap surgical replantation and reconstructions (Shakouri and Wollina, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Tanshinone, a lipophilic compound of Danshen, has been classified into four types based on its structural diversity: tanshinone IIA, cryptotanshinone, tanshinone I (Tan I), and dihydroisotanshinone I (DT) [ 18 ]. In clinical practice, Danshen is used for the treatment of various diseases, including cardiovascular diseases [ 19 ], cerebrovascular diseases [ 18 , 20 ], Alzheimer’s disease [ 21 ], PD [ 22 ], and renal injury [ 23 ]. Danshen is widely used for the treatment of cardiovascular disorders and its aqueous extract has shown anticancer as well as antioxidant effects [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice, Danshen is used for the treatment of various diseases, including cardiovascular diseases [ 19 ], cerebrovascular diseases [ 18 , 20 ], Alzheimer’s disease [ 21 ], PD [ 22 ], and renal injury [ 23 ]. Danshen is widely used for the treatment of cardiovascular disorders and its aqueous extract has shown anticancer as well as antioxidant effects [ 19 ]. Moreover, Danshen has been widely used in the treatment of central nervous system diseases.…”
Section: Introductionmentioning
confidence: 99%